2016
DOI: 10.1038/bjc.2016.120
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human phase I study of the DNA-repair inhibitor DT01 in combination with radiotherapy in patients with skin metastases from melanoma

Abstract: Background:DT01 is a DNA-repair inhibitor preventing recruitment of DNA-repair enzymes at damage sites. Safety, pharmacokinetics and preliminary efficacy through intratumoural and peritumoural injections of DT01 were evaluated in combination with radiotherapy in a first-in-human phase I trial in patients with unresectable skin metastases from melanoma.Methods:Twenty-three patients were included and received radiotherapy (30 Gy in 10 sessions) on all selected tumour lesions, comprising of two lesions injected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…However, no tests have yet been performed in blood cells. Here, we tested the effects of AsiDNA, the form of Dbait molecules used in the clinic (19), on the treatment of malignant blood cells and the toxicity of combined treatment to human blood cells. All tests were performed on human cells, as mouse blood cells have been shown to contain 50-fold less DNA-PK, one of the main targets of Dbait, than human blood cells (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no tests have yet been performed in blood cells. Here, we tested the effects of AsiDNA, the form of Dbait molecules used in the clinic (19), on the treatment of malignant blood cells and the toxicity of combined treatment to human blood cells. All tests were performed on human cells, as mouse blood cells have been shown to contain 50-fold less DNA-PK, one of the main targets of Dbait, than human blood cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is often used for the treatment of cancer, such as non-Hodgkin lymphoma, Hodgkin lymphoma, and all types of leukemia and the addition of AsiDNA could increase the efficacy of such treatment. We previously demonstrated in a first-in-man clinical trial that AsiDNA does not increase local toxicity of the irradiation (19). Treating lymphomas by combining treatment with AsiDNA and radiotherapy is a potentially promising method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pharmacological form called AsiDNA (or DT01), has been tested in phase I clinical trial on melanoma in association with radiotherapy. Two studies show the selective increase of cancerous cells sensitization [39,40]. Preclinical studies showed a chemo-sensitization of metastatic colorectal and liver cancers with AsiDNA [41].…”
Section: Targeting Dna-pk With Inhibiting Moleculesmentioning
confidence: 98%
“…This strategy sensitizes tumors to DNA damaging therapies such as radiotherapy and chemotherapy (15)(16)(17)(18). The first-in-human phase I trial, combining AsiDNA to radiotherapy to treat patients with skin metastases from melanoma showed encouraging results, with 30% of complete responses (19). We anticipated that AsiDNA could potentiate PARPi activity in BRCA proficient cells by inhibiting HR and establishing a transient state of BRCAness.…”
Section: Introductionmentioning
confidence: 99%